New emerging targets in cancer immunotherapy: the role of Cluster of Differentiation 40 (CD40/TNFR5). (12th June 2019) - Piechutta, Manuel; Berghoff, Anna Sophie
Abstract : Cluster of differentiation 40 (CD40) is a member of the tumour necrosis factor family and a new immune-modulating target in cancer treatment. B cells, myeloid cells and dendritic cells can express CD40 and mediate via the ligand cluster of differentiation 40 ligand (CD40L) cytotoxic T cell priming under physiological conditions. Therapeutically, recombinant CD40L molecules, intratumour application of adenoviral vectors leading to CD40L expression and agonistic monoclonal CD40 antibodies are currently tested in various cancer entities for their immune-modulating potential. Early clinical trials suggest safety for agonistic CD40 antibodies with encouraging antitumour effects. Adverse events encompass cytokine release storm, hepatoxicity, thromboembolic events and were so far reported to be clinically manageable and transient. Ongoing studies investigate CD40 activation in combination with chemotherapy, radiation, targeted therapies and immunomodulatory agents. Further studies are awaited to specifically identify patients with the greatest clinical benefit based on predictive biomarkers.